Meningkatan Kemampuan Membaca Suku Kata Melalui Aplikasi Solite Kids pada Anak Gangguan Spektrum Autisme Ringan Kelas III di SLB C Muzdalifah Medan - Hajadahni, Khairunisa; Zulmiyetri, Zulmiyetri; Nasri, Yosa Yulia; Rahmahtrisilvia, Rahmahtrisilvia (Indo-MathEdu Intellectuals Journal, 2026)
This study aimed to describe the process of learning syllable reading using the Solite Kids application and to prove the improvement in students’ syllable reading ability. This research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of two meetings with stages of planning, implementation, observation, and reflection. The research subjects were two students, ARH and LZS. Data were collected through observation and syllable reading tests. The results showed that the learning process using the Solite Kids application was carried out systematically, gradually, and in an enjoyable manner. Students became more focused, active, and interested in participating in the learning activities. In addition, the use of visual and audio features in the application helped students understand letter sounds and syllables. The students’ syllable reading ability improved significantly from the initial condition to the end of cycle II. ARH improved from 34.28% to 85.71%, while LZS improved from 48.57% to 88.57%. Based on these findings, it can be concluded that the Solite Kids application is effective as a learning medium to improve syllable reading ability in students with mild autism spectrum disorder in grade III at SLB C Muzdalifah Medan.